Penerapan Metode Dept First Search pada Pendeteksian Daerah Wisata Berbasis Android - Kurnia Yahya (PROGRESS, 2020)
This application uses the Android operating system which is one of the most popular mobile phone operating systems currently combined with Google Map, which is a web-based virtual world map service provided by Google. This application can be used as a medium of navigation and information, especially for the location of tourist attractions in the city of Makassar. The system development uses the Location Based Service (LBS) method. The product of this development is a mobile-based GIS application that has an Android operating system or platform. After testing the application that has been made, it can be concluded that the Application for Searching for Tourism Objects with the Depth First Search Method in South Sulawesi Province is based on Android which can help users / users obtain information about tourist objects in South Sulawesi.